Mechanism of dissipative-soliton-resonance generation in fiber laser mode-locked by real saturable absorber - Du, Wenxiong; Li, Heping; Li, Junwen; Wang, Pinghe; Zhang, Shangjian; Liu, Yong (Optics express, 2018)
Generation of dissipative soliton resonance (DSR) is numerically investigated in an all-normal-dispersion Yb-doped fiber laser mode-locked by a real saturable absorber (SA). In the simulation model, the SA includes both the saturable absorption and reverse saturable absorption (RSA) effects. It is found that the RSA effect induced by the SA material itself plays a dominant role in generating the DSR pulses. We also systematically analyze the influence of key SA parameters on the evolution of DSR pulses in the cavity. Our simulation results not only offer insight into the underlying mechanism of DSR generation in mode-locked fiber lasers by means of real SAs, but also provide a guideline for engineering SA parameters to generate optical pulses with the highest possible energy.